Effects of exercise on the formation of life-wide and value orientations of university students. - Marchenko O.U (Kharkov National Pedagogical University, 2011)
In this paper we consider the common interests of the students responsible for their hobbies in their spare time and the formation of values of individual physical education students as a basis for self-motivation. In the experiment participated 70 students. Classes are held during the school year in the amount of 4 hours per week. Determined the level of impact studies on the structure and hierarchy of values of students.